Dictionary of atheism, skepticism, & humanism - Cooke, Bill (Prometheus Books, 2006)
Atheism -- Anthropocentric conceit -- Atheism -- Atheism, ethical implications of -- Cosmic modesty -- Transcendental temptation -- Skepticism -- Critical common-sensism -- Critical receptiveness -- Fallibilism -- Inquiry, tools of -- Reliabilism -- Skepticism -- Skepticism, core principles of -- Humanism -- Agathonism -- Cosmic perspective -- Eupraxsophy -- Good life, the -- Humanism, foundations of -- Humanist virtues -- Moral truisms shared by us all -- Paideia -- Value meaning -- Wide reflective equilibrium